The influence of social media on students of second-cycle institutions in Tamale and its implications - Taufic Yabang Mohammed; Kukura Yirinibe Philip; Kanita Labaran (Journal of Social, Humanity, and Education, 2024)
Purpose: This study investigated the influence of social media on students in second-cycle institutions in Tamale. It concentrates on its relationship with academic performance, learning ability, writing skills, and gender disparities in usage patterns. Methodology/approach: A purposive sample method was employed to select 150 students from secondary schools in Tamale. Data were collected through surveys and interviews using both qualitative and quantitative approaches to explore how social media affects students’ academic experiences. Results/Findings: Findings from this study indicate that the use of social media has a significant impact on students’ learning abilities, writing skills, and academic performance. A significant number of learners reported becoming distracted with reduced concentration because they spent excessive time on the sites, leading to possible health challenges and a sedentary lifestyle. The results also indicated that gender differences exist in social media usage patterns, among others, which affect school performance. Limitations: One limitation of this research is that it had a small sample size and may not represent all students found within second-cycle institutions. This further implies that this research is constrained to a particular geographical area, limiting its generalizability. Contribution: This study contributes to the understanding of how social media influences students in second-cycle institutions, highlighting the need for educators and policymakers to establish guidelines for responsible social media use to enhance academic success and mitigate its negative impacts.